Pendidikan Self Management Guidance dan Self Care terhadap Kualitas Hidup Pasien Hipertensi - Siswandi, Iyar; Hidayah, Syamsul; Chaerani, Reni; Anwar, Syamsul (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of self-management guidance and self-care education on the quality of life of hypertensive patients in the working area of the East Rasanae Community Health Center, Bima City. This research method uses a Quasi-experimental research design with pre-test and post-test with control. The results of the study showed that there was an increase in the quality of life score in the intervention group, namely 50,360, and the control group by 55,280, accompanied by a significance value of 0.008 (p < 0.05) and a calculated t value of - 2,788 (< t table (2.05954). Multivariate test The quality of sleep in the intervention group showed P-Value = 0.004. The conclusion is that there is an influence of self-management guidance education and hypertension self-care on the quality of life of hypertensive patients. Keywords: Hypertension, Quality of Life, Self-Management Guidance